LEGAL ANALYSIS OF THE REJECTION REGISTRATION INTERFAITH MARRIAGES - Peni Rinda Listyawati; Indah Setyowati; Latifah Hanim (International Journal of Law Reconstruction, 2020)
The purpose of this journal is to find out about the problem of the legal position of interfaith marriage which shows that interfaith marriage is prohibited or normatively not regulated and is not recognized by the state and cannot be registered based on positive law. Research method uses a normative juridical approach, secondary data types, data collection methods that are carried out by literature, and the internet. While the data analysis method was analyzed descriptively qualitatively. The research results obtained indicate that the legal provisions of marriage, either express or implicitly, do not regulate the granting of marriage between followers of different religions. This is because marriage is prohibited between two people who have a relationship which by their religion or other regulations prohibited from marriage does not mean that the provisions in Islam prohibit interfaith marriage, so interfaith marriage is prohibited so that marriages that are carried out under religious law are not legitimate.